Toward Universal Financial Inclusion in China : Models, Challenges, and Global Lessons - World Bank Group; People's Bank of China (World Bank and People's Bank of China, 2018)
China has achieved remarkable success in financial inclusion. China’s rate of account ownership – a basic metric of financial inclusion – has increased significantly in the past two decades and is now on par with that of other G-20 countries. Traditional financial service providers have dramatically increased the reach of the formal financial sector, including through the world’s largest agent banking network. China has also been an established leader in the fintech revolution, with new technology-driven providers transforming how millions of Chinese consumers make payments, borrow, save, invest, and insure themselves against risk.